A digital approach to restore a traumatized anterior tooth during the COVID-19 pandemic: A clinical report - Fernandes Lima Oliveira, Luiz Gustavo (2022)
Dental professionals are at increased risk of infection with the new coronavirus 2019 (COVID-19) due to face-to-face communication and exposure to saliva, blood and other body fluids. Digital approaches can reduce clinical time and contribute to limiting the risk of infection. The objective of this work was to report a digital approach to restoring a traumatized anterior tooth during the COVID-19 pandemic. A 28-year-old female with abnormal mobility in the crown of an upper anterior tooth with history of dental trauma in the adolescence. An initial screening was performed to check for signs and symptoms of possible COVID-19 infection. Cone Beam Computed Tomography images showed a crown fracture and the presence of external cervical resorption in the right permanent central incisor. The treatment plan consisted of rehabilitation of the fractured tooth through a restoration retained with a fiberglass post with a digital approach using an intraoral scanner, and computer-aided design and fabrication - CAD/CAM. Digital approaches in dentistry including intraoral scanners and CAD/CAM could contribute to reducing the risk of COVID-19 infection in patients and dentists during restorative treatments.